Konvergensi Pertumbuhan Ekonomi Kota dan Kabupaten Klaster Metropolitan Jawa Timur - Nanda Mutya Atmasari; Teguh Hadi Priyono; Sebastiana Viphindrartin (e-Journal Ekonomi Bisnis dan Akuntansi, 2020)
The determination of the territorial clusters serves as the target of territorial development policies in order to increase equitable distribution of economic, infrastructure, social and cultural growth throughout East Java. This study aims to determine whether there is a decline in the economic growth gap every year (sigma convergence) and whether there is an acceleration of low economic growth to high economic growth (convergence beta) in the cities and districts of the East Java metropolitan cluster on 2015-2018. This research uses secondary data. The analytical method used in this study is convergence analysis and panel data regression analysis. The results showed that there was no decrease in the economic growth gap every year (sigma convergence) and there was no acceleration of low economic growth to high economic growth (beta convergence) in cities and districts of the East Java metropolitan cluster on 2015-2018. The estimation results of the regression analysis for beta convergence, both absolute and conditional, also show that there is no convergence in cities and districts in the East Java metropolitan cluster in the research year. The HDI and PMTB variables have not been able to encourage convergence of economic growth in cities and regencies in the metropolitan cluster of East Java. .